2016
DOI: 10.1193/012116eqs022m
|View full text |Cite
|
Sign up to set email alerts
|

Building Typologies Prevalent in Northern Pakistan and Their Performance during the 2015 Hindu Kush Earthquake

Abstract: The M7.5 earthquake of 26 October 2015 resulted due to reverse faulting at an intermediate depth of 210 km within the northeast-trending tabular zone underneath the Hindu Kush region, with its epicenter located 45 km southwest of Jarm in Afghanistan. In Pakistan alone, the earthquake and subsequent aftershock swarm resulted in 280 fatalities, injuries to 1,770 persons, and notable damage to 109,123 buildings. A synopsis of observations is presented herein, covering details about seismotectonics, strong motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Unreinforced masonry load bearing (URM) walls have routinely been documented to exhibit poor seismic performance during moderate to severe earthquakes, resulting in partial or complete collapse of the building [1][2][3][4][5]. The observed poor seismic performance of URM buildings has highlighted the seismic hazard associated with this form of construction, and the need for further investigation to advance the understanding of aspects related to their seismic assessment and improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Unreinforced masonry load bearing (URM) walls have routinely been documented to exhibit poor seismic performance during moderate to severe earthquakes, resulting in partial or complete collapse of the building [1][2][3][4][5]. The observed poor seismic performance of URM buildings has highlighted the seismic hazard associated with this form of construction, and the need for further investigation to advance the understanding of aspects related to their seismic assessment and improvement.…”
Section: Introductionmentioning
confidence: 99%
“…One important failure observed in existing stone masonry buildings was vertical cracks at the joints between two walls as they were not properly tied, which may lead to the collapse of wall corners as observed in the past [58]. These types of failures in buildings were observed in 2005 Kashmir [3] and 2015 Hindu Kush earthquake [59]. Most of the damaged structures in the case study area were found to be unreinforced masonry.…”
Section: Observed Seismic Behavior Of Buildings In Past Earthquakesmentioning
confidence: 95%
“…Unreinforced stone masonry buildings were damaged due to lack of structural integrity caused by improper bonding of cross walls. Unreinforced masonry buildings exhibit brittle failure, sliding off the roof, and diagonal shear cracks in the walls [60], and these types of failures were observed in 2015 Hindu Kush earthquake as well [59]. Confined masonry structures, as opposed to unconfined masonry structures, are found to exhibit good seismic performance and high energy dissipation capacity [60].…”
Section: Observed Seismic Behavior Of Buildings In Past Earthquakesmentioning
confidence: 99%
“…The Himalayan, Karakoram, and Hindu Kush fault nexus represents one of the most seismically active regions in the world [9]. The location of northern Pakistan on this syntaxis is characterized by increased seismicity owing to the convergence of the Eurasian and Indian plates, with the latter slipping northwards beneath the former at a rate of 37 -48 mm/year [3].…”
Section: Tectonics and Seismicity Of Northern Pakistanmentioning
confidence: 99%